G473(P)Nutritional adequacy of Prader-Willi syndrome children on restricted diets: A 10 year review from a multidisciplinary clinic. (7th April 2014) - Smith, C; Guildford, N; Livesey, A; Crook, D; Kanumakala, S
Abstract : Aims: A vital component of the management of Prader-Willi Syndrome (PWS) is strict control of dietary intake whilst ensuring sufficient nutrition to prevent deficiencies. Surprisingly however there is very limited data in the literature surrounding this. Our observational study sought to describe mean caloric intake, proportion of energy contributed by macronutrients and identify common micronutrient deficiencies. Method: PWS children attending our specialist multidisciplinary clinic complete weighed 3 day food diaries as part of their routine assessments. Analysis is completed using a specific computer package with results expressed as % of intake against UK reference nutrient intakes (RNI's) adjusted for age and sex. Data was retrospectively reviewed from case notes. Results: 35 food diaries were returned from 11 PWS children (age range 1.1–12 years) 5 males and 6 females between August 2002 – March 2013. Mean caloric intake was 69.5% RNI (Range 38–103%). A mean lower caloric % of RNI was seen in the younger children (<_ 5 years, n = 20) 66.8% compared to the older children (6–12 years n = 15) 73.1%. There was no obvious difference in the intake between males and females (68.8% vs. 70.8%). The mean proportions of % energy from fat, carbohydrate and protein (compared to UK recommendations) were 25% (35%), 58.8% (50%) and 15.8% (15%) respectively. 4 patients contributing a total of 10 food diaries over the collection period showed <20% total energy from fat. A Spearman correlation co efficient showed a significant (r = –0.57) inverse trend for greater micronutrient deficiencies with greater caloric restrictions. Incidence of <100% RNI for calcium and iron was 20% and 31% respectively. Insert graph Conclusion: Mean caloric intake in our PWS children was on average 30% less than the RNI's. The contribution proportions of macronutrients identified some concern of over restriction of fat (<20%) associated with increased risk for inadequate intake of polyunsaturated fatty acids. A reasonably strong correlation between caloric restriction and micronutrients intakes below the RNI should be noted and all results highlight care is required to carefully balance the restricted diets of nutritionally vulnerable PWS children.